“The Influence of Community Perceptions of Cibitung Tengah Village, Tenjolaya District, Bogor Regency on BUMDes Performance.” - Djafar, Harmi Ibnu; Cleopatra, Maria; Sahrazad, Sara (Jurnal USAHA, 2025)
This study aims to identify and analyze the perceptions of village communities towards the performance of BUMDes in Cibitung Tengah village, Tenjolaya sub-district, Bogor district. This study was participated by 54 people, who were taken randomly and filled in several questions that were distributed using a questionnaire for data collection.  In this study, data analysis was carried out using descriptive analysis techniques, linear regression analysis, classical assumption tests, and hypothesis testing. All of this was done using the Statistical Package for the Social Scienses (SPSS) version 26 analysis program application. The results showed that the effect of X on Y was significant, with a significance value of 0.000 <0.05 and an F-count value of 25.491. In conclusion, if H1 is accepted, then the effect of X on Y is significant..Keywords: BUMDes, Community Perception, Performance Management